2019
DOI: 10.4236/ojmsi.2019.74010
|View full text |Cite
|
Sign up to set email alerts
|

Survival Analysis of Factor Affects Survival Time of Hypertension Patients

Abstract: Hypertension is a major long-term health condition and a leading modifiable risk factor for cardiovascular disease and death. The aim of this study was to examine major factors that affect survival time of hypertension patients under follow-up. We considered a total of 430 random samples of hypertension patients who had been under follow up at Yekatit-12 Hospital in Ethiopia from January 2013 to January 2019. Four parametric accelerated failure time distributions: Exponential, Weibull, Lognormal and loglogisti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 25 publications
3
3
0
Order By: Relevance
“…Although this current study did not find any relationship between genders with patients a systolic blood pressure and the survival time until hypertension-related death; this finding is similar with previous research finding by Ref. 33 . But other studies in Ethiopia and India have reported that the covariate gender does not have any association with hypertension 35 , 36 .…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Although this current study did not find any relationship between genders with patients a systolic blood pressure and the survival time until hypertension-related death; this finding is similar with previous research finding by Ref. 33 . But other studies in Ethiopia and India have reported that the covariate gender does not have any association with hypertension 35 , 36 .…”
Section: Discussionsupporting
confidence: 91%
“…However, many researchers reported that there were no significant association between smoking and SBP of hypertension patients, and they concluded that there is no causal relationship 32 , 34 .The current study found that the patients who do not use alcohol had better survival probability than those who use alcohol. Similarly, Ayalew et al indicated that Alcohol use is a potential risk factor of hypertension and they also found Hypertension was significantly higher in individuals who use alcohol than those who did not use 33 .…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…These findings are agreed with previous researchers’ findings 15 17 . In this study, the finding regarding the relationship between place of residence of patients and survival time until hypertension associated death was similar with finding in Addis Ababa Ethiopia reported that place of residence has a significant effect on hypertension patients' survival time 14 . Moreover, we found that a family history of hypertension disease was a statistically significant risk factor for death in hypertension patients; this finding is consistent with the findings of other researchers 18 .…”
Section: Discussionsupporting
confidence: 88%
“…The study reveals that patients who did not use alcohol did not use Khat and did not smoke tobacco had a better survival probability than those who used alcohol, Khat and smoking tobacco. Similarly, Ayalew et al indicated that alcohol use is a potential risk factor for hypertension, and they also found hypertension was significantly higher in individuals who use alcohol than in those who did not use it 14 . This study finds that there is a strong dependence between SBP, FBS, and survival time of hypertension patients at AMGH, and suggests that joint model analysis rather than separate model analysis for such kind of dependence outcomes, clinical and medical studies.…”
Section: Discussionmentioning
confidence: 94%